Beneficial rhizobacteria Pseudomonas simiae WCS417 induce major transcriptional changes in plant sugar transport. (29th August 2020) - Desrut, Antoine; Moumen, Bouziane; Thibault, Florence; Le Hir, Rozenn; Coutos-Thévenot, Pierre; Vriet, Cécile
Abstract: Plants live in close relationships with complex populations of microorganisms, including rhizobacterial species commonly referred to as plant growth-promoting rhizobacteria (PGPR). PGPR are able to improve plant productivity, but the molecular mechanisms involved in this process remain largely unknown. Using an in vitro experimental system, the model plant Arabidopsis thaliana, and the well-characterized PGPR strain Pseudomonas simiae WCS417r ( Ps WCS417r), we carried out a comprehensive set of phenotypic and gene expression analyses. Our results show that Ps WCS417r induces major transcriptional changes in sugar transport and in other key biological processes linked to plant growth, development, and defense. Notably, we identified a set of 13 genes of the SWEET and ERD6-like sugar transporter gene families whose expression is up- or down-regulated in response to seedling root inoculation with the PGPR or exposure to their volatile compounds. Using a reverse genetic approach, we demonstrate that SWEET11 and SWEET12 are functionally involved in the interaction and its plant growth-promoting effects, possibly by controlling the amount of sugar transported from the shoot to the root and to the PGPR. Altogether, our study reveals that PGPR-induced beneficial effects on plant growth and development are associated with changes in plant sugar transport. Abstract : The plant sugar transporters SWEET11 and SWEET12 are functionally involved in the interaction between Arabidopsis thaliana and the plant growth-promoting rhizobacteria Pseudomonas simia e WCS417.